Non-technical skills and gastrointestinal endoscopy: a review of the literature. Issue 2 (29th March 2017) - Hitchins, Charlotte R; Metzner, Magdalena; Edworthy, Judy; Ward, Catherine
Abstract : Background: Non-technical skills (NTS) have gained increasing recognition in recent years for their role in safe, effective team performance in healthcare. Gastrointestinal endoscopy is a procedure-based specialty with rapidly advancing technology, significant operational pressures and rapidly changing 'teams of experts'. However, to date there has been little focus on the effect of NTS in this field. Objectives: This review aims to examine the existing literature on NTS in gastrointestinal endoscopy and identify areas for further research. Method: A systematic search of MEDLINE, Embase, Cochrane Library, PsychINFO, CINAHL Plus and PubMed databases was performed using search terms Non-Technical Skills, Team Performance or Team Skills, and Endoscopy, Colonoscopy, OGD, Gastroscopy, Endoscopic Retrograde Cholangio-Pancreatography or Endoscopic Ultrasound. Results: Eighteen relevant publications were found. NTS are deemed an essential component of practice, but so far there is little evidence of their integration into training or competency assessment. Those studies examining the effects of NTS and team training in endoscopy are small and have variable outcome measures with limited evidence of improvement in skills or clinical outcomes. NTS assessment in endoscopy is in its early phases with a few tools in development. Conclusions: The current literature on NTS in gastrointestinal endoscopy is limited. NTS, however, are deemed an essential component of practice, with potential positive effects on team performance and clinical outcomes. A validated reliable tool would enable evaluation of training and investigation into the effects of NTS on outcomes. There is a clear need for further research in this field.